Strategi Partisipasi Masyarakat Desa Dalam Peningkatan Kualitas Hidup Melalui Rehabilitasi Rumah Tidak Layak Huni di Kabupaten Pulau Morotai - Suryadi S. Abdullah; Firjal Firjal (Jurnal Ilmiah Wahana Pendidikan, 2022)
This article aims to examine the strategy of community participation in improving the quality of life through the movement to rehabilitate uninhabitable houses in Pangeo Village, Morotai Island Regency. Quality of life has a direct link with poverty; one of the standards for measuring the degree of quality of life is the feasibility of residential houses. In Morotai Island Regency, the phenomenon of unsuitable residential houses is a problem being faced by the community. However, in the midst of the problem of residential houses there is a participatory effort built by the community to improve the degree of quality of life through the rehabilitation of uninhabitable houses. The research design uses a qualitative descriptive method. Collecting data using observation techniques, interviews and documentation. Meanwhile, data analysis was carried out through data reduction, data presentation and drawing conclusions. This study reveals that the movement for community participation in overcoming the inadequacy of residential houses is driven by social values, namely Bari. The transformation of new values ​​first emerged from the awareness of the limited access to the economy of the people, whose professions are farmers and fishermen. On the other hand, government policies through the Rehabilitation of Uninhabitable Houses (RTLH) are still not on target due to the influence of socio-political factors in the village. Finally, decision making is still not optimal due to the strong domination of sectoral politics in the village.